Terkabulnya Perceraian dalam Keadaan Hamil - Setiyawan, Imas (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Marriage is a permanent relationship between two people who are legally recognized by the community concerned based on the applicable marriage regulations. The form of marriage depending on the local culture can vary and the goals can also vary. However, generally marriages are exclusive and recognize the concept of infidelity as a violation of marriage. Marriage is generally entered into with the intention of forming a family. Legal marriage ties are proven by documents in the form of a marriage certificate. But there are lots of various kinds of obstacles faced during the household so that divorce occurs.